Cationic pullulan nanogel as a safe and effective nasal vaccine delivery system for respiratory infectious diseases. Issue 9 (2nd September 2018) - Nakahashi-Ouchida, Rika; Yuki, Yoshikazu; Kiyono, Hiroshi
ABSTRACT: The mucosal surfaces of the respiratory and gastrointestinal tracts are continuously exposed to countless beneficial and pathologic antigens. These mucosal surfaces are thus equipped with an immune system that is unique from those elsewhere in the body; this unique system provides the first line of immune surveillance and defense against pathogen invasion. The sophisticated immune induction machinery in the aero–digestive tract involves mucosa-associated lymphoid tissues, including nasopharyngeal- and gut-associated lymphoid tissues, for the generation of antigen-specific humoral and cellular immune responses. Consequently, nasal or oral immunization with an appropriate vaccine delivery vehicle prompts the induction of protective immunity in both the mucosal and systemic compartments, leading to a double layer of protection against pathogens. To harness the benefits of mucosal vaccines, various mucosal antigen delivery vehicles are under development, and a cationic cholesteryl-group-bearing pullulan nanogel (cCHP nanogel) has emerged as a potent nasal vaccine delivery system for the induction of protective immunity against respiratory infections.